ANALYSIS WITH NESTED MULTINOMIAL LOGIT MODEL OF DEMAND FOR HEALTHCARE: AN APPLICATION IN KAYSERI PROVINCE - Zeynep Öztürk Yaprak; Eyyup Ecevit (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Determining the factors affecting the demand forhealthcare services are important in terms of providing health services moreeffectively and a more efficient health system. In addition, effectiveprovision of healthcare services is an important element in terms of basicsocio-economic development of countries. The primary aim of this study is todetermine the factors which affect the demand for healthcare services. In thatframework, factors related to household’s choice of applying to a healthcarefacility because of a health problem and the factors related to household’shealthcare facility choice are investigated using the data collected in Kayseriprovince with survey method. Within the scope of the study, Nested Logit Modelwas implemented to the data set using Full Information Maximum Likelihood(FIML) technique which estimates both decision levels simultaneously. Accordingto the results obtained, the factors which affect the choice of applying to thehealthcare facility were found as the educational level of the household head,severity of the disease and some health problem complaints. Among the factorswhich affect healthcare facility choice, educational level of the patientreduces the likelihood of applying to both public and private healthcarefacilities. Furthermore, likelihood of applying to public healthcare facilitiesreduces with the age of the patient.